Consumer behavior in e-Commercce: The role of ease, security, and price in purchase decisions on Tokopedia - Tirta, Yonathan Harun; Jumono, Sapto; Abddurahman, Abddurahman; Jatmiko, Jatmiko (Nur Science Institute, 2024)
This study examines the influence of perceived price, perceived security, and perceived ease of use on consumer purchase decisions on the Tokopedia application. This quantitative study uses an online survey distributed via Google Forms, targeting 100 respondents who are new and active Tokopedia users in the East Cengkareng area. The data were analyzed using multiple linear regression. The findings suggest that perceived ease of use, perceived security, and perceived price significantly affect consumer purchase decisions on the Tokopedia platform. This research contributes to understanding how key factors like convenience, security, and pricing perceptions shape online consumer behavior in e-commerce platforms, specifically Tokopedia. The study's results provide insights for e-commerce businesses, particularly Tokopedia, to enhance user experience by focusing on ease of use, improving security measures, and offering competitive pricing to influence purchasing decisions effectively.